APPLICATION OF SEMIOTIC REPRESENTATIONS IN MULTIVARIABLE CALCULUS THROUGH THE CONSTRUCTION OF PHYSICAL AND VIRTAUL ROLLER COASTER - Ruiz Castillo, Juan Carlos (2025)
This work presents the application of semiotic representations in multivariable calculus through the construction of a physical roller coaster and its modeling using GeoGebra as learning tools. The research was conducted with engineering students and explored how parametric equations and graphical representations help bridge the gap between abstract concepts and tangible understanding. The guiding research question is: How does the application of semiotic representations—through the use of GeoGebra and the physical construction of a roller coaster—impact engineering students’ understanding of fundamental multivariable calculus concepts? To address this question, the general  objective is to analyze how the application of semiotic representations through the use of GeoGebra and the physical construction of a roller coaster facilitates the understanding of multivariable calculus concepts in engineering students. The study revealed significant student interest, a solid understanding of parametric equations, and effective use of GeoGebra for visualizing 3D models, promoting better interdisciplinary knowledge integration.